The Role of Streptococcus Pneumoniae Carriage on Wasting Among Vaccinated Gambian Infants: A Longitudinal Analysis of a Birth Cohort - Zwane, Phindi (Department of Public Health and Family Medicine, 2023)
Wasting remains a serious public health problem, affecting 45 million children under five years old worldwide. A comprehensive understanding of the factors associated with child wasting is needed to inform interventions aimed at reducing and preventing wasting. Some studies have suggested that asymptomatic colonization of bacterial agents such as Streptococcus Pneumoniae (pneumococcus) may have negative impacts on child growth and nutritional status. The aim this study is to investigate the determinants of wasting and to assess the effect of pneumococcus carriage on wasting in children under the age of 2 years. The rationale, aim and objectives of the current study, along with the methodology, data analysis plan and ethical considerations are outlined in the protocol presented in Part A. Part B presents a manuscript that outlines and discusses the findings of the study. This study was a secondary analysis of data collected from 120 infants recruited at birth and followed up at regular intervals for two years. The data was collected in Rural Gambia between March 2013 and September 2015 as part of the Vaccination and Paediatric Microbiome Project. Nutritional status was classified using weight-for-length (WLZ), length-for-age (LAZ) and weight-forage (WAZ) z-scores for wasting, stunting and underweight respectively. Regression methods were used to evaluate the factors associated with both wasting, as a binary indicator, and weight-for-length z-scores among children aged 6-24 months. Over the two years of follow-up, 66.7% (80/120) of children had at least one episode of wasting with 36.3% (29/80) experiencing repeated episodes. About 47.5% (57/120) became stunted and 41.7% (50/120) became underweight. Nearly all the children (97.5%) became pneumococcus carriers at least once in the two years of follow up, with 50% of children becoming carriers within the first month of life. A small proportion of the children (15.8%) were born carriers. Carriage was lowest in the dry season but began to increase in the wet season until February, where it peaked. The median duration of carriage was 269.1 days (IQR: 70-508 days) Child age, mother's age at delivery, inflammation at birth, having at least one episode of wasting in the first six months of life, reporting a recent illness, and being observed in the rainy season had significant effects on WLZ scores in both the adjusted and unadjusted models. Pneumococcus carriage only had a significant association with WLZ scores in the adjusted model [RR: -0.18 (95% CI: -0.35 – - 0.01)], while low birthweight only had a significant association in the unadjusted model [RR: -0.78 (95% CI: -1.49 – -0.07)]. Mother's age at birth, inflammation at birth and reporting a recent illness was significantly associated with wasting as a binary indicator in both the adjusted and unadjusted models. Being observed in the rainy season decreased the odds of wasting, although, this association was only significant in the adjusted model [OR: 0.28 (95% CI: 0.10 – 0.75)]. Pneumococcus carriers had lower odds of wasting in the unadjusted model [OR: 0.29 (95% CI: -0.35 – 0.93)] and higher odds of wasting in the adjusted model [OR: 1.62 (95% CI: 0.70 – 3.74)]. Neither association was statistically significant. This study found low birthweight, early episodes of wasting, inflammation at birth and recent illness to be associated with wasting in children between the ages of 6-24 months. Targeting maternal nutrition during pregnancy, neonatal care and infant feeding practises may help reduce wasting among children between 6-24 months of age by reducing low birthweight, undernutrition, illness, and inflammation in early infancy. Further research is needed to understand the role of pneumococcus on child undernutrition.